High-thermal-conductivity polymer shaped composite phase change material and preparation method thereof
By microencapsulating paraffin and encapsulating it in the silicone polymer shell, combined with the thermal conductivity of expanded graphite, the deformation and cracking of HDPE substrates that may be caused by traditional phase change materials during the phase change process is solved, and the material is improved Stability and thermal conductivity.
Patent Information
- Application Number
- CN202411566305.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-17
AI Technical Summary
Traditional phase change energy storage materials increase thermal resistance during packaging, reduce heat transfer efficiency, and paraffin may cause deformation or rupture of HDPE substrate during phase change, affecting the stability and service life of the material.
High-density polyethylene (HDPE) is used as the carrier, and paraffin is microencapsulated by melt blending and in-situ polymerization to form a microencapsulated HDPE fixed paraffin composite material. Expanded graphite is used as the thermal reinforcement agent, and the silicone polymer shell is wrapped. Seal paraffin to prevent leakage and improve thermal conductivity.
The stable encapsulation of paraffin during the phase transition process is achieved, which avoids deformation and cracking of HDPE substrates, improves the stability and thermal conductivity of the material, and ensures the performance maintenance under multiple phase transition cycles.
Smart Images

Figure CN119320542A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of high thermal conductivity polymer shaped composite phase change material, in particular to a high thermal conductivity polymer shaped composite phase change material and a preparation method thereof. Background Art
[0002] Phase change materials refer to substances that change shape with temperature and can provide latent heat. The phase change latent heat storage or cold storage of phase change materials has the advantages of small temperature change and high energy storage density. It has broad application prospects in the fields of solar energy utilization, industrial waste heat and waste heat recovery, building heating and air conditioning energy saving. Traditional phase change energy storage materials need to be encapsulated in practical applications to prevent leakage, which increases the thermal resistance between the heat transfer medium and the phase change material, reduces the heat transfer efficiency and increases the cost. Polymer-shaped composite phase change materials solve the above problems well. The material is based on polymer materials, and phase change materials are dispersed in it to form an energy storage material. The phase change material is solid before and after the phase change, and the shape remains unchanged.
[0003] Since paraffin wax expands in volume when it melts and shrinks in volume when it solidifies, this volume change may cause deformation or rupture of the HDPE substrate, thereby affecting the overall stability and service life of the material. If the interface between HDPE and paraffin wax is not tightly bonded enough, or the cross-linked network structure of HDPE has large pores, paraffin wax may leak during the phase change process. Therefore, there are problems of leakage, frosting, and decreased thermal performance in HDPE shaped paraffin wax. Summary of the invention
[0004] The object of the present invention is to provide a high thermal conductivity polymer shaped composite phase change material and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A high thermal conductivity polymer shaped composite phase change material, comprising a polymer resin, a processing aid and a thermal conductive filler, an organic phase change material, a modifier, an initiator, an emulsifier, a dispersant and a catalyst;
[0007] Among them, the polymer resin adopts high-density polyethylene HDPE;
[0008] Processing aids include antioxidants, UV absorbers, and lubricants;
[0009] The thermal conductive filler is made of expanded graphite;
[0010] The organic phase change material uses paraffin wax;
[0011] The modifier is maleic anhydride MAH;
[0012] The initiator is diisopropylbenzene oxide DCP;
[0013] The emulsifier is toluene solvent;
[0014] The dispersant is melamine-modified urea-formaldehyde prepolymer;
[0015] The catalyst is composed of a main catalyst and a co-catalyst, the main catalyst is a transition metal compound of Group IV to VIII, and the co-catalyst is a metal organic compound of Group I to III;
[0016] Furthermore, the antioxidant is an amine antioxidant, the ultraviolet absorber is UV-326, and the lubricant is fatty acid amide.
[0017] Furthermore, the main catalyst is any one of TiCl4, TiCl3, and VOCl3, and the co-catalyst is mainly an alkyl aluminum compound.
[0018] A method for preparing a high thermal conductivity polymer shaped composite phase change material comprises the following steps:
[0019] Step 1: Put the expanded graphite into a jaw crusher for preliminary crushing, and crush it into smaller particles. After the preliminary crushing, the expanded graphite particles enter the hammer crusher for further particle refinement. The expanded graphite after particle refinement is sieved to remove particles that do not meet the requirements and obtain a particle size distribution that meets the requirements;
[0020] Step 2: Modify high-density polyethylene (HDPE), and graft the modifier to HDPE by melt grafting. The specific method is: add HDPE, maleic anhydride (MAH) and diisopropylbenzene (DCP) into a twin-screw extruder, and melt extrude the mixture through the twin-screw extruder. During the extrusion process, the material melts at high temperature and undergoes a grafting reaction. During the reaction, the modifier is grafted onto the HDPE molecular chain to form a graft copolymer.
[0021] Step 3: Add the modified HDPE into a twin-screw extruder, add the melted paraffin, stir and mix for 10 minutes, then add the expanded graphite, stir and mix for 30 minutes to fully mix the components to form a uniform melt;
[0022] Step 4: Microencapsulate the melt composite material by in-situ polymerization. The specific steps are as follows:
[0023] S1, adding toluene solvent and melamine-modified urea-formaldehyde prepolymer into a mixer reactor and stirring to obtain an emulsion, slowly adding the melt while stirring to prevent agglomeration, and continuing stirring until a uniform emulsion is formed;
[0024] S2, add appropriate amount of antioxidant, ultraviolet absorber, lubricant, and stir and mix for 10 minutes;
[0025] S3, adding silane monomers and catalysts that can polymerize to form silica gel polymers. Under the action of the catalyst, the silane monomers will be adsorbed on the surface of the core material and prepare for polymerization reaction. The active center of the main catalyst reacts with the monomer molecules to form active chain segments, and then structural units are continuously added to the chain until the required polymer chain length reaches a certain extent and the reaction stops. The co-catalyst helps the main catalyst maintain its activity and remove harmful substances in the system through alkylation reaction, reduction reaction, etc.
[0026] S4. Check the pH value of the emulsion and adjust the pH value of the emulsion to 7;
[0027] S5, reacting at 40° C. for 4 hours, the silane monomer gradually polymerizes to form a silica gel polymer shell layer, which completely encapsulates the HDPE shaped paraffin composite material to form a microencapsulated HDPE shaped paraffin composite material;
[0028] S6. After the polymerization reaction is completed, the microencapsulated HDPE shaped paraffin composite material is placed in an oven, the curing temperature is controlled at 65° C., and the reaction is carried out at this temperature for 2 hours. The microencapsulated HDPE shaped paraffin composite material is cured to ensure the stability and durability of the shell layer;
[0029] S7, placing the immobilized microencapsulated HDPE shaped paraffin composite material into a washing machine, suspending the microcapsules in a washing medium, washing by stirring, centrifuging, filtering or washing columns, etc., removing unreacted monomers and impurities, and obtaining a pure microcapsule product, placing the microencapsulated HDPE shaped paraffin composite material into an oven, controlling the drying temperature to 55° C., and drying at this temperature for 20 minutes to obtain a dried microencapsulated HDPE shaped paraffin composite material;
[0030] Step 5: Place the microencapsulated HDPE shaped paraffin composite material into a hot pressing equipment mold, heat the mold to 54°C, and heat the microencapsulated HDPE shaped paraffin composite material in the mold at 54°C. Apply a certain pressure through the hot pressing equipment to solidify the melt in the mold.
[0031] Compared with the prior art, the invention has the following beneficial effects: using expanded graphite as a thermal conductivity enhancer, high-density polyethylene as a carrier, and paraffin as a phase change material, a microencapsulated HDPE shaped paraffin composite material is prepared by melt blending, in-situ polymerization and hot pressing molding process; a silica gel polymer is prepared by in-situ polymerization, and the HDPE shaped paraffin is encapsulated to obtain a microencapsulated HDPE shaped paraffin composite material; the polymer film completely encapsulates the HDPE shaped paraffin composite material to form a phase change material microcapsule to prevent leakage and improve thermal conductivity, thereby solving the problem that the paraffin will undergo volume change when it is melted. The volume of HDPE shaped paraffin wax composite materials expands during the phase change process, and shrinks during solidification. This volume change may cause deformation or rupture of the HDPE substrate, and paraffin wax leaks during the phase change process, thus affecting the overall stability and service life of the material. Therefore, the microencapsulated HDPE shaped paraffin wax composite materials can still maintain stable performance in multiple phase change cycles. The microencapsulated HDPE shaped paraffin wax composite materials have better fluidity and dispersibility, and are easy to process and apply in various substrates. The polymer film not only completely covers the core material, but also closely combines with the core material surface through chemical bonds, thereby improving the stability and durability of the microcapsules.
[0032] Maleic anhydride MAH is grafted onto HDPE by melt grafting method. Polar groups are introduced into the HDPE molecular chain, which can increase the surface energy of HDPE and generate stronger interaction between it and paraffin, thereby improving the compatibility between the two, reducing the phase separation between HDPE and paraffin, and improving the uniformity and stability of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of the method for preparing the high thermal conductive polymer shaped composite phase change material of the present invention;
[0034] Figure 2 The present invention is a flow chart of the preparation of melt composite material microencapsulation. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example
[0037] See also Figure 1-2, the embodiment provided by the present invention: a high thermal conductivity polymer shaped composite phase change material, including polymer resin, processing aid and thermal conductive filler, organic phase change material, modifier, initiator, emulsifier, dispersant and catalyst;
[0038] Among them, the polymer resin adopts high-density polyethylene HDPE;
[0039] The processing aids include antioxidants, ultraviolet absorbers, and lubricants. The antioxidants include amine antioxidants, the ultraviolet absorbers include UV-326, and the lubricants include fatty acid amides.
[0040] The thermal conductive filler is made of expanded graphite;
[0041] The organic phase change material uses paraffin wax;
[0042] The modifier is maleic anhydride MAH;
[0043] The initiator is diisopropylbenzene oxide DCP;
[0044] The emulsifier is toluene solvent;
[0045] The dispersant is melamine-modified urea-formaldehyde prepolymer;
[0046] The catalyst is composed of a main catalyst and a co-catalyst, the main catalyst is a transition metal compound of Group IV to VIII, the co-catalyst is a metal organic compound of Group I to III, the main catalyst is any one of TiCl4, TiCl3, and VOCl3, and the co-catalyst is mainly an alkyl aluminum compound;
[0047] A method for preparing a high thermal conductivity polymer shaped composite phase change material comprises the following steps:
[0048] Step 1: Put the expanded graphite into a jaw crusher for preliminary crushing. After the expanded graphite is crushed into smaller particles, it is put into a hammer crusher for further particle refinement. The expanded graphite after particle refinement is screened to screen out 90-150μm expanded graphite. The expanded graphite particle size of 90-150μm can not only ensure the uniform dispersion of graphite in the composite material, but also maintain good processing performance and mechanical properties. After particle refinement, the expanded graphite has a larger specific surface area and a more uniform particle size distribution, which helps to improve its adsorption performance, flame retardancy and thermal stability;
[0049] Step 2: Modifying high-density polyethylene (HDPE): grafting maleic anhydride (MAH) onto HDPE by melt grafting. The specific method is as follows: adding HDPE, maleic anhydride (MAH) and diisopropylbenzene (DCP) into a twin-screw extruder, heating to a temperature range of 160°C-180°C, controlling the main speed of the extruder to 80rpm / min, and the feeding speed to 20rpm / min, and melt-extruding the mixture through the twin-screw extruder. During the extrusion process, the material melts at high temperature and undergoes a grafting reaction. During the reaction, MAH is grafted onto the HDPE molecular chain to form a HDPE graft copolymer.
[0050] Step 3: Add 35 parts by weight of modified HDPE into a twin-screw extruder, control the temperature at 160°C, add 65 parts by weight of paraffin after melting, stir and mix for 10 minutes, then add 10 parts by weight of expanded graphite, stir and mix for 30 minutes, so that the components are fully mixed to form a uniform melt;
[0051] Step 4: Microencapsulate the melt composite material by in-situ polymerization. The specific steps are as follows:
[0052] S1. Add toluene solvent and melamine-modified urea-formaldehyde prepolymer into a mixer reactor, perform shear emulsification at a speed of 1600 r / min for 5 min to prepare a phase change material emulsion, slowly add the melt, stir while adding to prevent agglomeration, and continue stirring until a uniform emulsion is formed. The melamine-modified urea-formaldehyde prepolymer is used to improve the dispersibility and uniformity of the phase change material in the emulsion, thereby improving the overall performance of the emulsion;
[0053] S2, adding 0.02 parts by weight of antioxidant 1010, 0.02 parts by weight of ultraviolet absorber UV-326, and 0.02 parts by weight of lubricant fatty acid amide, stirring and mixing for 10 minutes to improve the long-term stability of the emulsion or dispersion system;
[0054] S3, adding silane monomers and catalysts that can polymerize to form silica gel polymers, using toluene solvent to effectively dissolve the silane monomers participating in the in-situ polymerization, and maintaining a good dispersion state of the silane monomers in toluene, which is conducive to their uniform distribution on the surface of the core material in the subsequent polymerization reaction. At the same time, the active center of TiCl4 reacts with the monomer molecules to form active chain ends, and then continuously adds structural units to the chain until the required polymer chain length reaches a certain extent and stops the reaction. The alkyl aluminum compound helps the main catalyst to maintain its activity and remove harmful substances in the system through an alkylation reaction. Under the action of the catalyst, the silane monomers will be adsorbed on the surface of the core material and are ready for polymerization reaction;
[0055] S4. Check the pH value of the emulsion with a pH meter, and adjust the pH value of the emulsion by gradually adding ammonium chloride NH4CI. Ammonium chloride dissolves in water, and ammonium ions undergo hydrolysis to generate monohydrated ammonia and hydrogen ions, making the solution acidic. The pH value of the emulsion is neutralized to 7 by acidity. The specific method is as follows:
[0056] First, the initial pH of the emulsion was measured using a pH meter;
[0057] Then, a small amount of ammonium chloride was gradually added to the solution, and the solution was stirred thoroughly after each addition. After each addition, the pH value of the solution was measured using a pH meter to monitor its changes;
[0058] Finally, adjust the amount of ammonium chloride added based on the reading on the pH meter. If the pH of the solution is below 7, continue to add ammonium chloride slowly. If the pH begins to rise and approaches 7, reduce the amount of ammonium chloride added to avoid over-addition. Once the pH of the solution reaches 7, stop adding ammonium chloride.
[0059] S5, reacting at 40°C for 4 hours, the monomer molecules react chemically on the surface of the core material, forming covalent bonds and gradually cross-linking into a network structure, the network structure gradually thickens and expands to the entire core material surface, and finally forms a dense polymer film, which completely encapsulates the HDPE shaped paraffin composite material to form a phase change material microcapsule;
[0060] S6. After the polymerization reaction is completed, the microencapsulated HDPE shaped paraffin composite material is placed in an oven, the curing temperature is controlled at 65° C., and the reaction is carried out at this temperature for 2 hours. The microencapsulated HDPE shaped paraffin composite material is cured to ensure the stability and durability of the shell layer;
[0061] S7, placing the fixed microencapsulated HDPE shaped paraffin composite material into a washing machine, suspending the microcapsules in the washing medium, washing by stirring, centrifuging, filtering or washing columns, etc., removing unreacted monomers and impurities to obtain a pure microcapsule product, placing the microencapsulated HDPE shaped paraffin composite material into an oven, controlling the drying temperature to 55° C., and drying at this temperature for 20 minutes;
[0062] Step 5: Place the microencapsulated HDPE shaped paraffin composite material into the mold of the hot pressing equipment, heat the mold to 54°C, and melt the microencapsulated HDPE shaped paraffin composite material in the mold at 54°C. Apply a certain pressure through the hot pressing equipment to solidify the melt in the mold. During the hot pressing process, the lamellar structure of the expanded graphite is compressed and rearranged to form a denser thermal conductive network.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high thermal conductivity polymer shaped composite phase change material, characterized in that: Including polymer resins, processing aids and thermal conductive fillers, organic phase change materials, modifiers, initiators, emulsifiers, dispersants and catalysts; Among them, the polymer resin adopts high-density polyethylene HDPE; Processing aids include antioxidants, UV absorbers, and lubricants; The thermal conductive filler is made of expanded graphite; The organic phase change material uses paraffin wax; The modifier is maleic anhydride MAH; The initiator is diisopropylbenzene oxide DCP; The emulsifier is toluene solvent; The dispersant is melamine-modified urea-formaldehyde prepolymer; The catalyst consists of a main catalyst and a co-catalyst. The main catalyst is a transition metal compound of Group IV to Group VIII, and the co-catalyst is a metal organic compound of Group I to Group III.
2. The high thermal conductivity polymer shaped composite phase change material according to claim 1, characterized in that: The antioxidant is an amine antioxidant, the ultraviolet absorber is UV-326, and the lubricant is fatty acid amide.
3. The high thermal conductivity polymer shaped composite phase change material according to claim 1, characterized in that: The main catalyst is any one of TiCl4, TiCl3, and VOCl3, and the co-catalyst is mainly an alkyl aluminum compound.
4. A method for preparing a high thermal conductivity polymer shaped composite phase change material, characterized in that: The following steps are involved: Step 1: Place the thermal conductive filler in a jaw crusher for preliminary crushing to break it into smaller particles. After the preliminary crushing, the thermal conductive filler particles are further refined in a hammer crusher. The refined particles are sieved to remove particles that do not meet the requirements and obtain a particle size distribution that meets the requirements. Step 2: Modify the polymer resin, and graft the modifier to the polymer resin by melt grafting. The specific method is: add the polymer resin, the modifier and the initiator into a twin-screw extruder, and melt extrude the mixture through the twin-screw extruder. During the extrusion process, the material melts at a high temperature and a grafting reaction occurs. During the reaction, the modifier is grafted onto the polymer resin molecular chain to form a graft copolymer. Step 3: Add the modified HDPE into a twin-screw extruder, add the organic phase change material after melting, stir and mix for 10 minutes, then add the thermal conductive filler, stir and mix for 30 minutes to fully mix the components to form a uniform melt; Step 4: Microencapsulate the melt composite material by in-situ polymerization. The specific steps are as follows: S1, adding an emulsifier and a dispersant into a mixer reactor and stirring to obtain an emulsion, slowly adding the melt while stirring to prevent agglomeration, and continuing stirring until a uniform emulsion is formed; S2. Add appropriate amount of processing aid and stir and mix for 10 minutes; S3, adding monomers and catalysts that can polymerize to form silica gel polymers, the monomers will be adsorbed on the surface of the core material under the action of the catalyst and are ready to undergo polymerization reaction; S4. Check the pH value of the emulsion and adjust the pH value of the emulsion to 7; S5, reacting at 40° C. for 4 hours, the monomers gradually polymerize to form a silica gel polymer shell layer, completely encapsulating the composite material of the polymer resin shaped organic phase change material, thereby forming a microencapsulated composite material of the polymer resin shaped organic phase change material; S6. After the polymerization reaction is completed, the composite material of the microencapsulated polymer resin-shaped organic phase change material is placed in an oven, the curing temperature is controlled at 65° C., and the reaction is carried out at this temperature for 2 hours. The composite material of the microencapsulated polymer resin-shaped organic phase change material is cured to ensure the stability and durability of the shell layer; S7, placing the immobilized microcapsules into a washing machine, suspending the microcapsules in a washing medium, washing by stirring, centrifuging, filtering or washing columns, etc., removing unreacted monomers and impurities, and obtaining pure microcapsule products, placing the microcapsules into an oven, controlling the drying temperature at 55° C., and drying at this temperature for 20 minutes to obtain dried microcapsules; Step 5: Place the microcapsules into a hot pressing mold, heat the mold to 54°C, melt the microcapsules in the mold at 54°C, and apply a certain pressure through the hot pressing equipment to solidify the melt in the mold.
Citation Information
Cited By
Low-thermal-resistance phase change heat conduction material and preparation method thereof
CN120988482A
Low-thermal-resistance phase change heat conducting material and preparation method thereof
CN120988482B